PRACTICAL ARGUMENTATION IN AMERICAN POLITICAL DISCOURSE: Analysis of President Barack Obama’s State of the Union Address - Keburia, Mariam (Online Journal of Humanities ETAGTSU, 2018)
This paper is an attempt to analyze practical reasoning and practical argumentation schemes in the speeches of the 44th President of the United States – Barack Obama. It looks into the State of the Union Addresses delivered annually in the United States Congress (2009-2012) and focuses on the selected text of 2010, applying Critical Discourse Analysis (CDA) as an analytical framework. Emphasis is put on the stated values behind the practical reasoning – analysis has shown that the Claims for action and Goals are guided by the values of unity, fairness and responsibility. Claims for Action and Means-goals’ relations to the set Goal of the identified practical argument are strong and reasonable. This paper also identifies common rhetorical devices used by the speaker to achieve persuasive rationalization of the advocated measures. Full Text (PDF)